2019
DOI: 10.3389/fbioe.2019.00211
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized Adipose Tissue Hydrogel Promotes Bone Regeneration in Critical-Sized Mouse Femoral Defect Model

Abstract: Critical-sized bone defects fail to heal and often cause non-union. Standard treatments employ autologous bone grafting, which can cause donor tissue loss/pain. Although several scaffold types can enhance bone regeneration, multiple factors limit their level of success. To address this issue, this study evaluated a novel decellularized human adipose tissue (DAT) hydrogel as an alternative. In this study, DAT hydrogel alone, or in combination with adipose-derived stromal/stem cells (ASC), osteo-induced ASCs (OI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 58 publications
(82 reference statements)
1
29
0
3
Order By: Relevance
“…Mohiuddin et al demonstrated that a combination of decellularized adipose tissue (DAT) with adipose-derived stromal/stem cells (ASCs) is effective in the regenerative bone repair of mice critical-size femur defects. The group treated with the DAT hydrogel showed a higher deposition of OPN and collagen I as well as a higher bone area than the untreated group (Mohiuddin et al, 2019). Beyond that, porcine small intestinal submucosa (SIS) ECM was combined with true bone ceramic (TBC) and mineralized, to fabricate the tissue-derived ECM scaffold mSIS/TBC.…”
Section: Tissue-derived Decellularized Ecm Scaffoldmentioning
confidence: 99%
“…Mohiuddin et al demonstrated that a combination of decellularized adipose tissue (DAT) with adipose-derived stromal/stem cells (ASCs) is effective in the regenerative bone repair of mice critical-size femur defects. The group treated with the DAT hydrogel showed a higher deposition of OPN and collagen I as well as a higher bone area than the untreated group (Mohiuddin et al, 2019). Beyond that, porcine small intestinal submucosa (SIS) ECM was combined with true bone ceramic (TBC) and mineralized, to fabricate the tissue-derived ECM scaffold mSIS/TBC.…”
Section: Tissue-derived Decellularized Ecm Scaffoldmentioning
confidence: 99%
“…These methods combine biological (enzyme digestion), chemical, and physical processing steps to achieve the uniform and consistent manufacture of protein scaffolds depleted of contaminating genomic DNA and lipids. Obatala scientists, in collaboration with partners at Pennsylvania State University (PSU), Tulane University, and Western Ontario University, have developed and published on decellularized human adipose tissue-derived extracellular matrix (ECM) hydrogel, commercially termed “AdipoGel™” [ 70 , 83 , 84 , 85 , 86 ]. This hydrogel or scaffold is prepared using a combination of chemical and mechanical processing followed by protease digestion as a final modification prior to sterilization.…”
Section: Extracellular Matrix (Ecm) From Decellularized Adipose Timentioning
confidence: 99%
“…This hydrogel or scaffold is prepared using a combination of chemical and mechanical processing followed by protease digestion as a final modification prior to sterilization. In vitro, AdipoGel is capable of supporting adipose-derived stromal/stem cell (ASC) proliferation and adipogenic and osteogenic differentiation; in vivo, AdipoGel promotes critical-sized endochondral bone defect repair [ 83 , 84 , 85 ]. Furthermore, the decellularized adipose-derived scaffold can be chemically modified with thiol methacrylate and cross-linked to create a cytocompatible matrix that can be “tuned” to achieve biomechanical properties appropriate for the promotion of either soft or hard tissue regeneration [ 87 ].…”
Section: Extracellular Matrix (Ecm) From Decellularized Adipose Timentioning
confidence: 99%
See 1 more Smart Citation
“…Adipose tissue was obtained from LaCell LLC under an approved IRB protocol (Western IRB Study # 1138160, Puyallup WA) with written informed consent from donors (n = 3; BMI = 24:56 ± 2:52; age = 50 ± 5:7, mean ± standard deviation) undergoing elective abdominoplasty. Pooled adipose tissue from the three donors was decellularized and converted in to a prehydrogel (50 mg/mL) using the method described previously [35]. [36].…”
Section: Decellularized Adipose Tissue Hydrogel Preparationmentioning
confidence: 99%